Pengaruh Pemahaman Akuntansi Dan Literasi Digital Terhadap Kesiapan Kerja Calon Akuntan Di Era Digital 4.0 - Wayan Tari Indra Putri; Made Ayu Jayanti Prita Utami; Ni Nengah Lasmini; Wayan Eny Mariani (LPPM Universitas Sains dan Teknologi Komputer, 2025)
World has entered the Industrial Revolution Era 4.0 or also known as the Digital Era 4.0. In this era, the work industry changes dramatically and is different from the previous work industry, so that graduates or the workforce are expected to have the latest skills that match the needs of today's work industry. Digital literacy is said to be the ability to access, manage, understand, integrate, communicate, evaluate, and create information safely and appropriately using digital technology for work and entrepreneurship. Understanding of accounting and digital literacy is expected to be a provision for prospective accountants to be ready to enter the world of work that is full of changes and challenges. Based on this description, this study aims to determine whether accounting understanding and digital literacy affect partially or simultaneously on the job readiness of prospective accountants in the Digital Era 4.0.Respondents of this study were final semester students of managerial accounting study program, majoring in accounting, Bali State Polytechnic. The data obtained from this study came from questionnaires distributed to respondents. From the tests that have been carried out, it can be concluded that accounting understanding and digital literacy have an effect either partially or simultaneously on the job readiness of prospective accountants. A good understanding of accounting balanced with literacy skills is a provision for prospective graduates to be able to meet the needs of prospective accountants in the Digital Era 4.0.